الضرورة الشعرية عند النقاد حتى نهاية القرن الرابع الهجري وآراء المحدثين فيها (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research studies the poetic necessity according to the critics who were interested in poetry, and wrote criticized books chose between poetry and poets , and classified poetry into section , depending on meaning and pronunciation .Critics emphasized the unique nature of poetry ,this uniqueness made the poets question what was against then rules making apologies for it to keep it accepted . Critics looked at poetry as another level of expression and approved it with terms and conditions , such as / shame / judgement and poetry phenomena , such of it according to necesseties , critics had different views about necessities , some refused it , and described as ugliness that fades away by words water , while others approved it .Whatever opinion have the critics about necessities , it is aphenomenon that took their attention , some wrote whole books , and others chapters .In most cases , no one called it as mistake , and the lasting effect of poetry that has necessities keep it approved .يتناول البحث الضرورة الشعرية عند أهمّ النقاد الذين اهتموا بالشعر، وألفوا فيه كتباً ، وأطلقوا عليه أحكاماً، وفاضلوا بين الأشعار ، وصنّفوها معتمدين اللفظ والمعنى في أحكامهم . أكد النقاد الطبيعة الخاصة للشعر ، وهذه الخصوصية جعلت النحاة يقفون أمام ما خالف قواعدهم ، يلتمسون الأعذار لإبقائه في دائرة القبول ، أما النقاد فنظروا إلى الشعر على أنه مستوى آخر في التعبير واستحسنوه ، لكنهم وضعوا للشعر معاييرَ وأطلقوا حكم / العيب / على بعض الظواهر في الأشعار ، ومن بعض العيوب ما صنّفه النحاة ضرائر . اختلف النقاد في مواقفهم من الضرائر ، فمنهم من رفضها ووصفها بالقبح الذي يُذهب بماء الكلام ، ومنهم من استحسن بعضها ، ومهما يكن من أمر النقاد وموقفهم من الضرائر ، فإنها ظاهرة نالت اهتمامهم ، فمنهم من ألّف فيها كتاباً مستقلاً ، ومنهم من أفرد لها فصولاً من كتاب ، وفي أغلب الأحكام لم يُطلق عليها صفة الخطأ ، وإنّ خلود الأبيات التي تحمل ضرورات يبقيها في دائرة الاستحسان .